2001
DOI: 10.1046/j.1525-1594.2001.06895.x
|View full text |Cite
|
Sign up to set email alerts
|

Customized Bicarbonate Buffered Dialysate and Replacement Solutions for Continuous Renal Replacement Therapies: Effect of Crystallization on the Measured Levels of Electrolytes and Buffer

Abstract: The aim of this study was to investigate the impact of the addition of calcium to bicarbonate solutions for continuous renal replacement therapy (CRRT). We tested single bag (bicarbonate and calcium mixed 24 h before testing) and double bag solutions (mixed immediately before) with and without the addition of 4 mEq/L of acetate. Prescribed calcium varied from 0 to 5 mEq/L. All test solutions containing calcium showed crystallization at light microscopy. The double bag solutions decreased but did not prevent cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 19 publications
1
8
0
Order By: Relevance
“…Finally, in previous years, the possibility of calcium carbonate precipitation prevented the widespread use of premixed fluid bags [8,21,22]. In our study, visual inspection was negative at all times, and no clinically significant changes in calcium or bicarbonate concentrations were noticed.…”
Section: Discussionsupporting
confidence: 44%
“…Finally, in previous years, the possibility of calcium carbonate precipitation prevented the widespread use of premixed fluid bags [8,21,22]. In our study, visual inspection was negative at all times, and no clinically significant changes in calcium or bicarbonate concentrations were noticed.…”
Section: Discussionsupporting
confidence: 44%
“…Indeed, in our previous study, the delivered calcium concentration varied inversely with crystal precipitation. In the SB, crys‐tallization was greater and the delivered calcium was lower compared to DB (15). In addition, the test solution pH was alkaline for the bicarbonate‐buffered and acidic for the lactate‐buffered solutions.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study we have shown that when calcium and bicarbonate are mixed in the same bag, even immediately before testing, there is always a certain amount of precipitation. Consequently, the delivered dose of electrolytes and buffer is less than the prescribed dose (15). The impact of the presence of these precipitated crystals and the correlated changes in the electrolytic composition of these solutions on leukocyte function have not yet been investigated.…”
mentioning
confidence: 99%
“…First, the ideal prepackaged replacement solution should include a bicarbonate buffer instead of a lactate buffer. However, precipitation of crystals has been clearly documented, even when solutions containing calcium and bicarbonate are mixed immediately prior to use (37). While the implications of this are not entirely clear, it would seem prudent at this time not to use a bicarbonate‐based buffer solution.…”
Section: Disadvantagesmentioning
confidence: 99%